Characterization of Blood Surrogate Immune-Methylation Biomarkers for Immune Cell Infiltration in Chronic Inflammaging Disorders - Declerck, Ken; Vanden Berghe, Wim (Frontiers in Genetics, 2019)
Alzheimer’s disease (AD) and atherosclerosis are both chronic age- and inflammation-dependent diseases. In addition, atherosclerosis is frequently observed in AD patients indicating common involvement of vascular components in disease etiologies. Recently, epigenome-wide association studies have identified epigenetic alterations, and in particularly DNA methylation changes for both diseases. We hypothesized the existence of a common DNA methylation profile in atherosclerosis and AD which may be valuable as a blood-based DNA methylation inflammaging biomarker. Using publicly available 450k Illumina methylation datasets, we identified a co-methylation network associated with both atherosclerosis and AD in whole blood samples. This methylation profile appeared to indicate shifts in blood immune cell type distribution. Remarkably, similar methylation changes were also detected in disease tissues, including AD brain tissues, atherosclerotic plaques and tumors and were found to correlate with immune cell infiltration. In addition, this immune-related methylation profile could also be detected in other inflammaging diseases, including Parkinson’s disease and obesity, but not in multiple sclerosis, schizophrenia and osteoporosis. In conclusion, we identified a blood-based immune-related DNA methylation signature in multiple inflammaging diseases associated with changes in blood immune cell counts and predictive for immune cell infiltration in diseased tissues. In addition to epigenetic clock measurements, this immune-methylation signature may become a valuable blood-based biomarker to prevent chronic inflammatory disease development or monitor lifestyle intervention strategies which promote healthy aging.